Coexisting cancers: a mixture of neuroendocrine carcinoma and adenocarcinoma in the gallbladder. Issue 44 (November 2016) - Hu, Hai-Jie; Zhou, Rong-Xing; Tan, Yong-Qiong; Jing, Qiu-Yang; Ma, Wen-Jie; Yang, Qin; Wang, Jun-Ke; Wang, Shu-Jin; Cheng, Nan-Sheng; Li, Fu-Yu
Abstract: Background: Neuroendocrine carcinoma is rare with a proportion of less than 2% in gallbladder malignancies, cases of gallbladder neuroendocrine cell carcinoma coexisting with adenocarcinoma are exceptionally rare, and the prognosis is dismal. Methods: Herein, we presented an unusual case of poorly differentiated gallbladder neuroendocrine cell carcinoma coexisting with poorly differentiated adenocarcinoma who survived 20 months after the multimodal treatment (MT) of extended surgery and postoperative chemotherapy. Results: Our result indicated that for advanced gallbladder neuroendocrine cell carcinoma coexisting with adenocarcinoma, MT including extended surgical approach combined with postoperative chemotherapy may contribute to a relatively good survival outcome. Conclusion: MT may contribute to a relatively good survival outcome for advanced gallbladder neuroendocrine cell carcinoma coexisting with gallbladder adenocarcinoma.